Comparison of Panretinal Photocoagulation alone With Panretinal Photocoagulation plus Intravitreal Bevacizumab in Treatment of High Risk Proliferative Diabetic Retinopathy - RANA INTISAR UL HAQ, AHSAN MUKHTAR, MAZ, BUSHRA AKBAR (Journal of Fatima Jinnah Medical University, 2018)
Objective: To compare the panretinal photocoagulation (PRP) with PRP plus intravitreal Bevacizumab in treatment of high risk proliferative diabetic retinopathy in terms of mean change of neovascularization on disc (NVD). Design: It was a randomized controlled trial. Place and Duration of Study: This study was conducted at the Department of Ophthalmology, Armed Forces institute of Ophthalmology, Rawalpindi over 6 months period from November 2014 through April 2015. Patients and Methods: This study involved 60 consecutive patients of both genders aged between 20-65 years known to be diabetic for at least 10 years with HbA1C ≤7% presenting at Ophthalmology outdoor having high risk PDR. These patients were randomly allocated into two treatment groups. Patients allocated to Group-A received panretinal photocoagulation (PRP) in two sessions 2 weeks apart while patients in Group-B received single injection of intravitreal Bevacizumab (IVB) prior to 2 sessions of PRP as in Group-A. Outcome variable was mean clinical change of NVD described as percentage area of disc diameter affected by neovascularization on disc (NVD) regressed at 6 weeks follow-up. Results: Both the study groups were comparable in terms of mean age (p=0.568), mean duration of diabetes (p=0.763), mean BMI (p=0.395), mean HbA1C levels (p=0.289) and frequency of various age (p=0.795), genders (p=0.796), duration of diabetes (p=0.774), BMI (p=0.559) and HbA1C groups (p=1.000). The mean NVD at baseline was 44.87±4.18% in Group-A and 44.67±4.91% in Group-B without any statistically significant difference between the two groups (p=0.866). The mean NVD at follow-up was significantly lower in both the groups as compared to base line; Group-A (43.28±4.26% vs. 44.87±4.18%; p=0.000) and Group-B (38.47±4.74% vs. 44.67±4.91%; p=0.000). However, the mean post-treatment NVD was significantly lower in Group-B as compared to Group-A (38.47±4.74% vs. 43.28±4.26%; p=0.000) across all age, gender, duration of diabetes, BMI and HbA1C groups. The mean decrease in NVD was significantly higher in Group-B (6.20±1.13% vs. 1.58±0.74%; p=0.000) as compared to Group-A and this difference was significant across all age, gender, duration of diabetes, BMI and HbA1C groups. Conclusion: Combination therapy in the form of panretinal photocoagulation plus intravitreal Bevacizumab was found to be better with significantly lower mean NVD (38.47±4.74 vs. 43.28±4.26%; p=0.000) at follow-up as compared to panretinal photocoagulation alone. The mean decrease in NVD upon follow-up was significantly higher with combination therapy (6.20±1.13% vs. 1.58±0.74%; p=0.000) as compared to panretinal photocoagulation monotherapy.